Predictors of Learning Engagement in the Context of Online Learning During the COVID-19 Pandemic - Stan, Maria Magdalena; Topală, Ioana Roxana; Necşoi, Daniela Veronica; Cazan, Ana-Maria (Frontiers in Psychology, 2022)
In the context of the COVID-19 pandemic, which forced much if not all academic experiences to move to a virtual environment, exploring the possible antecedents of students’ engagement in online learning became a focal point of attention for teachers and researchers. The main aim of the present research is to analyze the predictive value of individual characteristics such as online self-efficacy, adaptability to uncertainty and sources of stress during online learning on learning engagement. We also aimed to highlight if these relationships could be mediated by the online self-regulated learning strategies, during the COVID-19 pandemic. The participants were 529 university students and the design was cross-sectional. The results showed significant associations of the sources of stress in online learning with self-efficacy, leaning engagement and self-regulated learning strategies. Self-regulated strategies – task strategies and goal settings represent mediators of stressors perceived by the students under the conditions of the sudden passage to online activity and online learning engagement. The most important self-regulation strategies seemed to be goal setting and task strategies, which confirm the need for a clear structure of learning in the context of online activities. The implications of this study reside in the increased awareness regarding how learning engagement in online learning can be predicted by individual characteristics.